2022
DOI: 10.1007/s00477-022-02239-6
|View full text |Cite
|
Sign up to set email alerts
|

Unified landslide hazard assessment using hurdle models: a case study in the Island of Dominica

Abstract: Climatically-induced natural hazards are a threat to communities. They can cause life losses and heavy damage to infrastructure, and due to climate change, they have become increasingly frequent. This is especially the case in tropical regions, where major hurricanes have consistently appeared in recent history. Such events induce damage due to the high wind speed they carry, and the high intensity/duration of rainfall they discharge can further induce a chain of hydro-morphological hazards in the form of wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…So far, no spatially nor temporally explicit model exists for landslide area density. However, four recent articles have explored the capacity of predicting landslide areas (Lombardo et al, 2021;Aguilera et al, 2022;Bryce et al, 2022;Moreno et al, 2022). All of them have returned suitable predictive performance, but still far from the match seen in the second panel of Figure 7, between observed and predicted landslide density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no spatially nor temporally explicit model exists for landslide area density. However, four recent articles have explored the capacity of predicting landslide areas (Lombardo et al, 2021;Aguilera et al, 2022;Bryce et al, 2022;Moreno et al, 2022). All of them have returned suitable predictive performance, but still far from the match seen in the second panel of Figure 7, between observed and predicted landslide density.…”
Section: Resultsmentioning
confidence: 99%
“…In their work, the authors exclusively estimated the potential landslide size at a given location, without informing whether the given location would have been susceptible in the first place. This limitation has been further addressed by Bryce et al (2022) and Aguilera et al (2022), implementing models that couple susceptibility and landslide area prediction together. Nevertheless, even in these cases, the absence of the temporal dimension in their work implies that no current datadriven model has even been capable to solve the landslide hazard definition (Guzzetti et al, 1999), jointly estimating where, when (or how frequently) and how large landslides may be in a given spatio-temporal domain.…”
Section: Introductionmentioning
confidence: 99%
“…This is something that has already been observed in other susceptibility studies , and it is usually interpreted under the assumption that upwardly concave morphologies would experience acceleration in terms of overland flows and thus lead to higher erosion and destabilization capacity (Ohlmacher, 2007). With regards to the slope exposition, we opted for a generally accepted strategy where the terrain aspect is decomposed into northness and eastness (Cama et al, 2017;Lombardo et al, 2020a;Samia et al, 2020;Bryce et al, 2022). Among the available contributions in Tawain, Lee (2013) indicated that slopes facing south and southeast hosted more frequently landslides than others during the Chi-Chi earthquake.…”
Section: Interpretation Of Covariate Effectsmentioning
confidence: 99%
“…In mountainous regions, natural hazards such as landslides, avalanches, floods, and debris flows can cause significant property damage and human casualties 1 . Landslides are triggered by earthquakes 2 4 , extreme meteorological events such as intense precipitation 5 and windstorms 6 – 9 , and anthropogenic activities 10 . Landslides alone have contributed to roughly $4.5 billion of economic loss between 1990 and 2017 according to the EM-DAT 11 , and approximately 58% of the fatalities and 69% of economic losses transpired in East and Southeast Asia, respectively.…”
Section: Introductionmentioning
confidence: 99%